2023
DOI: 10.3390/nu15010240
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Status Indicators as a Predictor of Achieving Remission at Week 14 during Vedolizumab Therapy in Patients with Ulcerative Colitis: A Pilot Study

Abstract: Background: The loss of response or failure to achieve remission to vedolizumab in ulcerative colitis (UC) patients is currently a major clinical problem. Recently, Nutritional Risk Index (NRI), Controlling Nutritional Status (CONUT), and Malnutrition Universal Screening Tool (MUST) have been suggested as a new prognostic factor of UC activity. Here, we aimed at confirmation of hypotezis that NRI, CONUT and MUST may be used as inexpensive and efficient predictive biomarkers of response in UC patients treated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
(30 reference statements)
0
0
0
Order By: Relevance
“…For instance, taking advantage of the results from the tofacitinib OCTAVE Induction 1 and 2 clinical trials, Lees CW et al could identify that baseline PMS, C-reactive protein (CRP) or cholesterol levels predict early clinical response [41]. Moreover, it has been reported that the nutritional status correlates with the response to VDZ, showing the non-responder patients an increased Malnutrition Universal Screening Tool (MUST) score at the initiation of therapy [42].…”
Section: Clinical Datamentioning
confidence: 99%
“…For instance, taking advantage of the results from the tofacitinib OCTAVE Induction 1 and 2 clinical trials, Lees CW et al could identify that baseline PMS, C-reactive protein (CRP) or cholesterol levels predict early clinical response [41]. Moreover, it has been reported that the nutritional status correlates with the response to VDZ, showing the non-responder patients an increased Malnutrition Universal Screening Tool (MUST) score at the initiation of therapy [42].…”
Section: Clinical Datamentioning
confidence: 99%